Genetic/Epigenetic Alteration and Tumor Immune Microenvironment in Intrahepatic Cholangiocarcinoma: Transforming the Immune Microenvironment with Molecular-Targeted Agents - Naoshi Nishida; Masatoshi Kudo (Liver Cancer, 2023)
Background: Intrahepatic cholangiocarcinoma (iCCA) is often diagnosed at an advanced stage, leading to limited treatment options and a poor prognosis. So far, standard systemic therapy for advanced iCCA has been a combination of gemcitabine and cisplatin. However, recent advancements in the understanding of the molecular characteristics of iCCA have opened new possibilities for molecular-targeted therapies and immunotherapy. Summary: Reportedly, 9–36% of iCCA cases have an inflamed tumor immune microenvironment (TME) based on the immune gene expression signature, which is characterized by the presence of immune cells involved in anti-tumor immune responses. The majority of iCCA cases have a non-inflamed TME with a lack of effector T cells, rendering immune checkpoint inhibitors (ICIs) ineffective in these cases. Interestingly, alterations in the fibroblast growth factor receptor (FGFR2) gene and IDH1/2 gene mutations are often observed in the non-inflamed TME in iCCA. Several mechanisms have been reported for the role of driver mutations on the establishment of TME unique for iCCA. For example, IDH1/2 mutations, which cause an increase in DNA methylation, are associated with the downregulation and hypermethylation of antigen processing and presentation machinery, which may contribute to the establishment of a non-inflamed TME. Therefore, inhibitors targeting IDH1/2 may restore the DNA methylation and expression status of molecules involved in antigen presentation, potentially improving the efficacy of ICIs. FGFR inhibitors may also have the potential to modulate immunosuppressive TME by inhibitingthe suppressor of cytokine signaling 1 and activating the interferon-γ signaling as a consequence of inhibition of the FGFR signal. From this perspective, understanding the molecular characteristics of iCCA, including the TME and driver mutations, is essential for the effective application of ICIs and molecular-targeted therapies. Key Messages: Combination approaches that target both the tumor and immune system hold promise for improving the outcomes of patients with iCCA. Further research and clinical trials are needed to validate these approaches and optimize the treatment strategies for iCCA.